Nursing her Amish neighbor [large type] - Perry, Marta (Perry, Marta. Brides of Lost Creek., 2021)
"Seeking a break from her nursing duties, Miriam Stoltzfus returns home to Lost Creek - and encounters her most difficult patient yet. Her childhood neighbor, Matthew King, is suffering after an accident left him injured and his younger brother dead. But he doesn't want anyone's help. Can Miriam guide him through his grief to prove he's still the strong, confident man she remembers?" -- Back cover.